Gomesin peptides prevent proliferation and lead to the cell death of devil facial tumour disease cells. - Fernandez-Rojo, M.; Deplazes, Evelyne; Pineda, S.; Brust, A.; Marth, T.; Wilhelm, P.; Martel, N.; Ramm, G.; Mancera, R.; Alewood, P.; Woods, G.; Belov, K.; et al. (2018)
The Tasmanian devil faces extinction due to devil facial tumour disease (DFTD), a highly transmittable clonal form of cancer without available treatment. In this study, we report the cell-autonomous antiproliferative and cytotoxic activities exhibited by the spider peptide gomesin (AgGom) and gomesin-like homologue (HiGom) in DFTD cells. Mechanistically, both peptides caused a significant reduction at G0/G1 phase, in correlation with an augmented expression of the cell cycle inhibitory proteins p53, p27, p21, necrosis, exacerbated generation of reactive oxygen species and diminished mitochondrial membrane potential, all hallmarks of cellular stress. The screening of a novel panel of AgGom-analogues revealed that, unlike changes in the hydrophobicity and electrostatic surface, the cytotoxic potential of the gomesin analogues in DFTD cells lies on specific arginine substitutions in the eight and nine positions and alanine replacement in three, five and 12 positions. In conclusion, the evidence supports gomesin as a potential antiproliferative compound against DFTD disease.